# Simplify g^2-20gh-g+20h.

### 2 Answers | Add Yours

If by simplify you mean factorize, we have to factorize: g^2 - 20gh - g + 20h

g^2 - 20gh - g + 20h

factorize the the common factor (g - 20h)

=> g(g - 20h) - 1(g - 20h)

=> (g - 1)(g - 20h)

**The factorized form is g^2 - 20gh - g + 20h = (g - 1)(g - 20h).**

The first step is to create groups of terms:

g^2-20gh-g+20h = (g^2-20gh)-(g-20h)

We'll factorize by g the first group:

g^2-20gh-g+20h = g(g - 20h) - (g - 20h)

We'll factorize by (g - 20h):

g^2-20gh-g+20h = (g - 20h)(g - 1)

**The simplified expresison is: g^2-20gh-g+20h = (g - 20h)(g - 1)**